Sistem Dan Prosedur Pengelolaan Arsip Di PT Insani Prima Konsultindo (IPK) - Dina Rosiana; Diva Ayu Santoso; Binti Muchsini (Badan Penerbit STIEPARI Press, 2024)
Implementation of Records Management Systems and Procedures (SPA) is a critical step in increasing the efficiency and accountability of information management in organizational and corporate environments. The scope is an analysis of the planning, implementation and effectiveness of SPA in optimizing storage, management and accessibility of records in a company. The methodological approach involves in-depth evaluation of existing systems and procedures, identification of company needs, and design and implementation of appropriate SPA. The main focus of SPA includes document categorization, version management, access permission management, and security measures to protect the authenticity and confidentiality of information. The importance of developing and implementing appropriate SPA as a foundation for effective records management. The implications of these findings have a positive impact on companies, providing a solid framework for transparent and efficient information governance. These findings can be a valuable guide for other companies seeking to improve the quality of their records management.